(untitled) (Research, Society and Development, 2023)
Hospital Dentistry promotes comprehensive health for hospitalized patients, avoiding infections that can harm critical patients. The dentist plays an essential role in the diagnosis, planning and execution of clinics approach focused on the quality of life of patients. Knowing this, this proposed subject emerged with the aim of verifying how dentistry students see the performance and function of the dentist in the hospital environment and its importance for the restoration of the general health status of the hospitalized patient. A study was carried out at the Dental Polyclinic of the State University of Amazonas with academics on the admission of Hospital Dentistry in the curriculum. Of these academics, 95.5% are aware that hospital dentistry is a qualification in dentistry. On the other hand, 77.6% of the undergraduates had never been follow a call atendt hospital environment. of those academics that already follow up, only 11.9% were in an ICU environment. 94% of the research volunteers reconizes that it is essential for the dentist to have knowledge in the hospital area. 92.5% are favorable the inclusion of the discipline in the curricular grade of the Dentistry course, as 70.1% of this group answered that they need more theoretical knowledge to perform treatment in hospitalized patients. Thus, it can be noted that the inclusion of hospital dentistry in the curricular curriculum of the Dentistry course would generate an increase in theoretical-practical-scientific knowledge for academics, providing greater skills for care in ICUs and hospitals.